2010
DOI: 10.1016/j.fusengdes.2010.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Particle-in-cell simulation of magnetic-assisted electrostatic confinement device

Abstract: In order to enhance the fusion reaction rate in Inertial Electrostatic Confinement devices, it is necessary to increase the ion density with low cathode current and low background pressure. In order to accomplish the requirement, the authors suggest Magnetic-assisted Electrostatic Confinement (MEC) scheme. The MEC relies on controlling the ion motion by applying an axial magnetic field to a system with cylindrical electrodes. In order to clarify the fundamental performances of the MEC device, Particle-in-Cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In a practical discharge we would expect non-zero I wire due to ion charge exchange. A similar concept has been considered by Tomiyasu et al [8] for the case of a glow discharge placed under an external pulsed magnetic field. The advantage of using the RS-MIS is that it allows operation at lower-pressures, and produces a magnetic field which is radially-varying and permanent.…”
Section: Future Work and Implicationsmentioning
confidence: 87%
“…In a practical discharge we would expect non-zero I wire due to ion charge exchange. A similar concept has been considered by Tomiyasu et al [8] for the case of a glow discharge placed under an external pulsed magnetic field. The advantage of using the RS-MIS is that it allows operation at lower-pressures, and produces a magnetic field which is radially-varying and permanent.…”
Section: Future Work and Implicationsmentioning
confidence: 87%
“…Takamatsu et al [3] reported a ten-times increase in number of fusion reactions as well as an increase in overall efficiency, all when ion sources were employed in the setup. The control of the ion motions during the device operation by applying an axial magnetic field was simulated by Tomiyasu et al [4]. Following these studies, Kurilenkov et al [5] investigated the effects of virtual cathode, and single-and double-well potentials on the IECF reactor operation when an electric discharge is applied.…”
Section: Introductionmentioning
confidence: 99%